Development and Evaluation of an Adaptive Scrum Model for Wedding Organizer Systems Using UML and ISO 25010 - Haisyam Maulana; Rian Dwicahya Supriatman; Tuti Rohayati; Nana Yudi Permana (Journal of INISTA, 2026)
This study proposes an adaptive Scrum model for developing a web-based Wedding Organizer system by integrating structured modeling and iterative development practices. Unlike conventional Scrum implementations, the proposed model incorporates Unified Modeling Language use case diagrams for defining product backlog, working hour-based effort estimation for sprint planning, and a client validation loop to enhance continuous user involvement. The system was developed through iterative sprints aligned with wedding preparation phases, ensuring better synchronization between development activities and real-world workflows. An analyst role within the development team was introduced to maintain consistency between system modeling and implementation. System evaluation was conducted based on ISO/IEC 25010, focusing on functional suitability and usability aspects. The results indicate that all system features operate as expected, and usability testing using the System Usability Scale achieved a score of 82.5, categorized as Excellent. The findings demonstrate that the proposed model improves requirement clarity, planning accuracy, and user involvement, leading to enhanced system usability and development efficiency. This study contributes a structured and practical approach to adapting Scrum for event-based application domains, particularly in Wedding Organizer systems.